Up-regulation of long non-coding RNA H19 ameliorates renal tubulointerstitial fibrosis by reducing lipid deposition and inflammatory response through regulation of the microRNA-130a-3p/long-chain acyl-CoA synthetase 1 axis - Yali Jiang; Feng Ma; Jing Wang; Xiaojing Chen; Lu Xue; Xinping Chen; Jinping Hu (Non-coding RNA Research)
Long non-coding RNA (lncRNA) H19 is an extensively studied lncRNA that is related to numerous pathological changes. Our previous findings have documented that serum lncRNA H19 levels are decreased in patients with chronic kidney disorder and lncRNA H19 reduction is closely correlated with renal tubulointerstitial fibrosis, an essential step in developing end-stage kidney disease. Nonetheless, the precise function and mechanism of lncRNA H19 in renal tubulointerstitial fibrosis are not fully comprehended. The present work utilized a mouse model of unilateral ureteral obstruction (UUO) and transforming growth factor-β1 (TGF-β1)-stimulated HK-2 cells to investigate the possible role and mechanism of lncRNA H19 in renal tubulointerstitial fibrosis were investigated. Levels of lncRNA H19 decreased in kidneys of mice with UUO and HK-2 cells stimulated with TGF-β1. Up-regulation of lncRNA H19 in mouse kidneys remarkably relieved kidney injury, fibrosis and inflammation triggered by UUO. Moreover, the increase of lncRNA H19 in HK-2 cells reduced epithelial-to-mesenchymal transition (EMT) induced by TGF-β1. Notably, up-regulation of lncRNA H19 reduced lipid accumulation and triacylglycerol content in kidneys of mice with UUO and TGF-β1-stimulated HK-2 cells, accompanied by the up-regulation of long-chain acyl-CoA synthetase 1 (ACSL1). lncRNA H19 was identified as a sponge of microRNA-130a-3p, through which lncRNA H19 modulates the expression of ACSL1. The overexpression of microRNA-130a-3p reversed the lncRNA H19-induced increases in the expression of ACSL1. The suppressive effects of lncRNA H19 overexpression on the EMT, inflammation and lipid accumulation in HK-2 cells were diminished by ACSL1 silencing or microRNA-130a-3p overexpression. Overall, the findings showed that lncRNA H19 ameliorated renal tubulointerstitial fibrosis by reducing lipid deposition via modulation of the microRNA-130a-3p/ACSL1 axis.